Accounting Information System and Business Organizations: Bachelor of Science in Business Administration - Garry Alfonsius (Universal Institute of Professional Management, 2021)
Organizations depend on information systems to stay competitive. Information is just as much a resource as plant and equipment. Productivity, which is crucial to staying competitive, can be increased through better information systems. Accounting, as an information system, identifies, collects, processes, and communicates economic information about an entity to a wide variety of people. Information is useful data organized such that correct decisions can be based on it. A system is a collection of resources related such that certain objectives can be achieved. An accounting information system (AIS) is a collection of resources, such as people and equipment, designed to transform financial and other data into information. This information is communicated to a wide variety of decision makers. AISs perform this transformation whether they are essentially manual systems or thoroughly computerized.